Back Cover: Erasable Superconductivity in Topological Insulator Bi2Se3 Induced by Voltage Pulse (Adv. Quantum Technol. 9/2021). Issue 9 (14th September 2021) - Le, Tian; Ye, Qikai; Chen, Chufan; Yin, Lichang; Zhang, Dongting; Wang, Xiaozhi; Lu, Xin
Abstract : Emergent superconductivity is observed in the local mesoscopic point‐contacts on the topological insulator Bi2 Se3 by applying a voltage pulse through the Ag contacts. The superconductivity can be erased with thermal cycles by warming up to high temperatures (300 K) and repeatedly induced by the voltage pulse at base temperature (1.9 K), suggesting a significance for designing new types of quantum devices. For further details, see article number 2100067 by Tian Le, Xiaozhi Wang, Xin Lu and co‐workers.